HAK-HAK KEWARISAN BANCI DALAM HUKUM ISLAM - Umar, Subehan Khalik (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2018)
Islamic jurisprudence has placed a sissy as one of the legal phenomena and their existence has made the study of Islamic law in the field of inheritance to be more comprehensive. The sissy (khunṣa) in Islamic inheritance law is only pinned to those who have multiple genitals. They are then identified based on the function of both genitals and defined their status based on the determination. Those who fail to pass through this process are then punished as an improper (muskilate) sissy. This group will get the smallest portion of inheritance from their portion while awaiting research on their final gender.